Avaliação do desempenho de gotejadores com uso de água residual na suinocultura - Franco, Daniel [UNESP] (2015)
The aim of the present work was to evaluate the application uniformity of water using the distribution uniformity coefficient (DU), Christiansen uniformity coefficient (UC) and statistical uniformity coefficient (SUC), besides determine the flow variation coefficient (FVC) using a Netafim brand 16060 Streamline model dripper tube, after its use with swine wastewater. The The experiment was done in Irrigation Laboratory of UNESP-FCA, Botucatu-SP campus. It have done in a dripper test bench using four sections of 6 meters dripper tubes, 32 emitters chosen, where the flow verified in the emitters was the following pressure: 45, 55, 65, 78kPa, with four repetitions for each dripper. After the test, the dripper tube was subordinated to 600 hours work with swine wastewater. It have done the same tests with the new dripper tube with 100, 200, 300, 400 and 500 hours of work with residual water. The obtained values with the new tube and after its use through 400 hours with swine wastewater for FVC were classified as good by ABNT chart (1987). Nevertheless, when reached 500 hours of work, the pressures 45 and 65 kPa show a FVC of 0.5 considerate medium by ABNT (1987) and with 600 hours of work, the evaluation in all pressures were classified as medium. The DU, UC and SUC, since initial test to 600 hours of work in bench were classified as excellent, according to Merriam & Keller (1978), despite of some drippers show partial obstruction through time. However, through the time, the DU and UC besides classified as excellent show a small decline in their values. Based in the obtained results, it is possible to conclude that after 600 dripper tube hours of use, the dripper keep satisfactory water application uniformity, the test showed the possibility of swine wastewater for dripper irrigation, without dripper obstruction problems in periods until 600 hours of use. For swine wastewater use in irrigation projects ...